Antimicrobial Activities of Extract of Andalas Endophytic Bacterial Fermentation Products in Overcoming Oral Cavity Infection - Dwi Hilda Putri; Ratih Rahayu; Dinda Sahara; Nurhelmi Nurhelmi; Violita Violita (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2019)
Dental and oral infection problems can be overcome using natural antimicrobial compounds from bacterial endophytic resulted from bacterial fermentation. This study aims to determine the effectiveness of extracts of Andalas endophytic bacterial fermentation products in treating oral cavity infections. Fermentation products was extracted using maceration methods. Antimicrobial activity of Andalas endophytic bacterial fermentation product was evaluated to S. mutans and C. albicans by disk diffusion method. The study showed that the optimum concentration of extract in inhibiting microbial growth that causes oral cavity infections was at 12.5%.